2011
DOI: 10.1364/oe.19.023054
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for using the binary approximation of continuously self-imaging gratings

Abstract: Diffractive Optical Elements (DOE), that generate a propagation-invariant transverse intensity pattern, can be used for metrology and imaging application because they provide a very wide depth of focus. However, exact implementation of such DOE is not easy, so we generally code the transmittance by a binary approximation. In this paper, we will study the influence of the binary approximation of Continuously Self-Imaging Gratings (CSIG) on the propagated intensity pattern, for amplitude or phase coding. We will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For practical implementation of a CSIG, binary approximations of the transmittance function have been considered [24]. But even with a binary-coded CSIG, the OTF is composed of sparse delta functions, as shown in Fig.…”
Section: Definitions Of Csig Merit Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…For practical implementation of a CSIG, binary approximations of the transmittance function have been considered [24]. But even with a binary-coded CSIG, the OTF is composed of sparse delta functions, as shown in Fig.…”
Section: Definitions Of Csig Merit Functionsmentioning
confidence: 99%
“…In [24], it has been demonstrated that, for an ideal CSIG, the OTF is composed of a central peak of relative weight N, where N is the number of diffracted orders, N peaks of relative weight 1 are located on the cutoff frequency ring, and N 2 ∕2 − N other peaks of relative weight 2 are located inside the cutoff frequency ring. If the CSIG is implemented with a binary grating, the relative weights of all peaks are slightly different from those ideal values.…”
Section: A Normalization Of the Otfmentioning
confidence: 99%
See 2 more Smart Citations
“…8(b), we can deduce that this global intensity pattern is composed by a propagation-invariant term and a propagation-dependant term under monochromatic illumination. Under incoherent and polychromatic illumination, it has been shown, for other self-imaging objects 8,9 , that the propagation-dependant term decreases because of a visibility factor due to the spectrum's width, and can be neglected after the panchromatic distance defined by:…”
Section: Design Rulementioning
confidence: 99%